2016
DOI: 10.3390/ijms17101723
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Role of Platelets: Translational Insights from Experimental Studies of Autoimmune Disorders

Abstract: Beyond their indispensable role in hemostasis, platelets have shown to affect the development of inflammatory disorders, as they have been epidemiologically and mechanistically linked to diseases featuring an inflammatory reaction in inflammatory diseases like multiple sclerosis, rheumatoid arthritis and inflammatory bowel disorders. The identification of novel molecular mechanisms linking inflammation and to platelets has highlighted them as new targets for therapeutic interventions. In particular, genetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 99 publications
1
27
0
Order By: Relevance
“…Injury leads to the activation of microglia in the dorsal horn of the spinal cord, which results in the release of cytokines and growth factors that excite nociceptive dorsal horn neurons, contributing to the development of central sensitization and hyperalgesia [120] as well as the pathogenesis of chronic pain [121,122]. It is important to note that chronic inflammatory processes are not specific to pain (e.g., autoimmune diseases, aging) [123,124] and may arise from acute immune challenges [125]. Therefore, other conditions that incite neuro-inflammatory responses may also lead to chronic pain and comorbid conditions.…”
Section: Potential Neurobiological Mechanisms Underlying Comorbid mentioning
confidence: 99%
“…Injury leads to the activation of microglia in the dorsal horn of the spinal cord, which results in the release of cytokines and growth factors that excite nociceptive dorsal horn neurons, contributing to the development of central sensitization and hyperalgesia [120] as well as the pathogenesis of chronic pain [121,122]. It is important to note that chronic inflammatory processes are not specific to pain (e.g., autoimmune diseases, aging) [123,124] and may arise from acute immune challenges [125]. Therefore, other conditions that incite neuro-inflammatory responses may also lead to chronic pain and comorbid conditions.…”
Section: Potential Neurobiological Mechanisms Underlying Comorbid mentioning
confidence: 99%
“…Given that platelets have been reported to accumulate in the synovial microcirculation in the antigen-induced arthritis model, they might provide an ideal platform for lymphocyte recruitment into the joint [60]. Platelets are newly recognized for their significant role in inflammatory diseases, including arthritis [61] and platelet depletion has been reported to ameliorate experimental arthritis [62]. Thus, lack of Asm secretion by platelets in Smpd1 -/- mice may be responsible for amelioration of arthritis severity reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…42 There are a number of studies which indicate that platelets, apart from their major role in cellular hemostasis, also participate in the development of autoimmune mechanisms, neurodegeneration and neuroinflammation. 43,44 There are many reports suggesting that platelets are chronically activated in neurodegenerative diseases. Platelet activation, degranulation and platelet-leukocyte interactions may affect the pathophysiology of neurodegenerative diseases, including MS.…”
Section: Role Of Blood Platelets In Neuro-inflammation and Neurodegenmentioning
confidence: 99%
“…58,59 In most EAE models, which are driven by Th1 or Th17 cells, inflammation starts with profound infiltration of the tissue by the major histocompatibility complex (MHC) Class II restricted CD4-positive T-cells, which is followed by microglia activation and macrophage recruitment into the lesions. 43 In EAE and MS, Th1 and Th17 cells infiltrate into the CNS through the BBB, where they become reactivated and initiate the destruction of myelin sheath (demyelination) and axonal/neuronal degeneration in MS. 2,60 It has also been demonstrated that IL-1β, IL-6, IL-23, and the transforming growth factor (TGF-β) are crucial for human Th17 differentiation from naive CD4-positive and CD45-positive peripheral blood lymphocytes. The TGF-β and IL-21 promote the polarization of Th17 cells from human naive CD4-positive T-cells.…”
Section: Role Of Blood Platelets In Neuro-inflammation and Neurodegenmentioning
confidence: 99%